Postmortem Findings in Patients with COVID19 Using Multiple Organ Core Needle Biopsies. (28th October 2021) - Harb, Z F; Mueller, J; Khan, A; Ravikumar, N; Tidswell, M
Abstract: Introduction/Objective: The coronavirus disease 2019 (COVID19) pandemic had caused more than 500, 000 deaths in the United States. Although it mainly manifests with respiratory symptoms, postmortem examination reveals that it is more of a systemic disease affecting mutliple body organs. Methods/Case Report: Postmortem needle core biopsies from multiple organs were obtained from 9 patients who died at our institution in the months of April and May of 2020 due to a confirmed SARS-CoV-2 infection by RT-PCR testing of nasopharyngeal swabs. The core biopsies from body organs included lungs (8), liver (7), kidneys (5), heart (2), spleen (2), and brain (2). Histopathological examination was performed in conjunction with a set of special and immunohistochemical stains. Electron microscopy examination was also done in 4 cases. Results (if a Case Study enter NA): The cohort consisted of 6 males and 3 females with a mean age of 70.4 years (range: 68–79). The majority had comorbidities (8/9) and presented with respiratory symptoms (9/9). The most significant postmortem findings were mainly in the lungs, including alveolar hemorrhage, hyaline membranes, fibrin thrombi, intraalveolar macrophages, type-2 pneumocyte hyperplasia, and interstitial myofibroblast reaction and collagen deposition. Immunohistochemical stains showed predominance of T-lymphocytes with a mixture of CD4 and CD8 positive cells. Examination of liver showed minimal to marked microvesicular and macrovesicular steatosis and centrilobular congestion and necrosis. Tissue from kidneys revealed mild to severe acute tubular injury. Microglial activation and Alzheimer type-II astrocytosis were noted in brain, and mild white pulp depletion was seen in the spleen. Electron microscopy showed the presence of foreign bodies suspicious for viral particles ranging in size from 52.6 to 97.9 nm in 2/4 cases. Conclusion: Our findings based on postmortem core needle biopsies confirm the observation that most severely affected patients have significant pulmonary pathology. However, other organs show findings that may lead to a better understanding of this disease. Postmortem examination will continue to be an invaluable tool for studying the pathologic manifestations of COVID-19.